DEVELOPMENT OF COMPUTERIZED FERTILIZER RECOMMENDATIONS FOR COCONUT (BASED ON FOLIAR ANALYSIS) USING A LOTUS 123 SOFTWARE PACKAGE SYSTEM - R.Z. MARGATE; M.I. SECRETARIA; S.S. MAGAT; L.M. ALFORJA (International Coconut Community, 1992)
A Lotus 123‑based system computer program was developed for fertilizer recommendation of local tall verieties and Dwarf x Tall hybrid coconuts using foliar analysis results. The computer program which is coded as PCA‑FERT. PRG. Version 1.0 utilized the average fertilizer recommendation formulated by Philippine Coconut Authority based on the Authority's 20 years; of research experience on the nutrition and fertilization of coconut in the country. As a first attempt towards the computerization of research outputs on coconut nutrition and fertilization, the program, should facilitate the faster assessment of existing coconut stands in terms of its nutritional status and fertilizer needs. The effective utilization of this program coupled with the researcher's knowledge and expertise on the use of foliar analysis results. will contribute much to the formulation of an accurate and reliable fertilizer recommendation.